2018
DOI: 10.18585/inabj.v10i2.390
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effect of Momordica charantia L. Fruit Ethanol Extract on Phagocytic Activity and Capacity of Mice Peritoneal Macrophages

Abstract: B ACKGROUND:The purpose of this research is to understand the secondary metabolites of Momordica charantia L. extract, as well as to disclose the potential of M. charantia extract in the phagocytic activity and capacity of peritoneum macrophages. METHODS:Examination of immunomodulatory effect was done by giving M. charantia ethanol extract on 5 treatment groups, given intra-peritoneally to mice daily. Echinacea extract as positive control and double distilled water as negative control were also given. On the 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The mechanism of flavonoids as antioxidants is by donating H atoms to stabilize free radicals. (23) Based on previous research, non-polar compounds of M. charantia L. fruit n-hexane fractions are terpenoid derivatives, namely cucurbits triterpenes. (24) Some of these compounds were Momordin I and Momordin II.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of flavonoids as antioxidants is by donating H atoms to stabilize free radicals. (23) Based on previous research, non-polar compounds of M. charantia L. fruit n-hexane fractions are terpenoid derivatives, namely cucurbits triterpenes. (24) Some of these compounds were Momordin I and Momordin II.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of the alkaloids and flavonoids are similar to those in other plants. Generally, flavonoid compounds can repair the immune system, while alkaloids have an immunomodulatory ability (Parawansah et al, 2018). Previous studies showed that flavonoid compounds can stimulate lymphocyte proliferation and increase the T-cell count and interleukin-2 (IL-2) activity.…”
Section: Discussionmentioning
confidence: 99%
“…The study used a different species, Staphylococcus epidermidis, but it is still in the same genus as S. aureus. (21) The potency of ethanol leaf extract of other herbal, Spondias pinnata, has been reported to improve the phagocytic activity of macrophage cells challenged with latex beads. (22) The different visualization between the active and inactive macrophages showed phagocytosis activity.…”
Section: Discussionmentioning
confidence: 99%